Knowledge Level on Milk Protein Consumption Towards Acne Vulgaris for Gym Users - Akmal, Mohammad Anis; Hazlianda, Cut Putri (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebaceous unit, with a polymorphic clinical picture consisting of various skin disorders. Whey protein is also associated with potential acne triggers and is used as a supplement by young people trying to increase muscle mass. Objectives: To find out the description of the knowledge of gym users on the relationship between consuming milk protein and the incidence of acne vulgaris. Methods: This research is a descriptive study using a cross-sectional study approach. The sample was selected using a non-probability sampling technique, namely consecutive sampling with a sample size of 67 people using a questionnaire. Results: 67 gym users were selected as samples where the knowledge in the good category was as many as 3 people (4,5%), followed by the adequate category with the number of 24 people (35,8%) and the less category of 40 people (59,7%). Most sources of information obtained about the relationship between consuming milk protein to the incidence of acne vulgaris are from social media. Conclusion: The level of knowledge of gym users at the Grand Olympus Gym regarding the relationship between consuming milk protein and the incidence of acne vulgaris in general less knowledge. Latar Belakang: Akne vulgaris (AV) adalah penyakit peradangan kronis dari unit pilosebasea, dengan gambaran klinis polimorfik yang terdiri dari berbagai gangguan kulit. Whey protein dikaitkan dengan potensi pemicu jerawat dan digunakan sebagai suplemen oleh usia muda yang mencoba meningkatkan massa otot. Tujuan: Untuk mengetahui gambaran pengetahuan para pengguna gym tentang hubungan antara mengonsumsi protein susu dengan kejadian akne vulgaris. Metode: Penelitian ini merupakan studi deskriptif dengan menggunakan pendekatan studi potong lintang. Sampel dipilih menggunakan teknik non-probability sampling yaitu consecutive sampling dengan jumlah sampel sebanyak 67 orang dengan menggunakan kuesioner. Hasil: Sebanyak 67 pengguna gym dipilih sebagai sampel dimana pengetahuan dengan kategori baik sebanyak 3 orang (4,5%), diikuti kategori cukup dengan jumlah 24 orang (35,8%) dan kategori kurang sebanyak 40 orang (59,7%). Sebagian besar sumber informasi yang didapatkan tentang hubungan antara mengonsumsi protein susu dengan kejadian akne vulgaris berasal dari media sosial. Kesimpulan: Tingkat pengetahuan pengguna gym di Grand Olympus Gym mengenai hubungan antara mengonsumsi protein susu dengan kejadian jerawat (acne vulgaris) secara umum berpengetahuan kurang.